Russian-Armenian scientific cooperation from the viewpoint of joint publication activity (on DBs «Web of Science Core Collection», «Scopus», Russian Science Citation Index for 2005-2014) - Y. V. Mokhnacheva (Библиосфера)
The Commonwealth of Independent States creation in 1991 was a new reality for cooperation and development of post-Soviet states. Russia and Armenia have long close and stable relations in the scientific-educational sphere. The article objective is to evaluate the joint Russian-Armenian documentary flow in various scientific fields for ten years (2005-2014). As the research information base three main resources were studied that allow analyzing the co-publication activity: «Web of Science Core Collection» (Thomson Reuters); Scopus (Elsevier); RISC (OLC «Scientific Electronic Library»). Research articles and reviews were considered. The Russian-Armenian documentary flow dynamics was studied with the differentiation by arrays: publications, whose authors are both the Russian and Armenian scientists; publication created with and without participation in major international collaborations; publications involving authors of third countries; publication without the participation of third countries authors. Evaluation indicators of the joint Russian-Armenian publication activity were: the publications number dynamics; average citation; frequency distribution of publications on periodicals; frequency distribution of joint publications on areas of knowledge. The study reveals growing the number of publications, whose authors are Russian and Armenian scientists working in large international collaborations (ATLAS, CMS Collaboration, ALICE Collaboration, etc.) recent years. Such publications citation is quite high: the level of citation exceeds the world average parameters two-seven times for these years. The level of the cited publication carried on without international collaborations is 62-155% of the world average indicators. The documentary flow out of collaborations, but with the participation of third countries authors has a varied dynamic with an average growth rate about 1% (WoS) to 2% (Scopus). The main co-author states as «third» countries are: Germany, Italy, the USA and the UK. Main cooperation between Russia and Armenia takes place in physics and astronomy (about 1/2 of joint publications); chemistry (8%) and biology (6%) and material science (6%). Sciences spectrum of joint research is represented by 23 branches of knowledge. The study results showed a high level of the Russian-Armenian scientific ties with good development potential.